Cyberdeterrence and Cyberwar - Libicki, Martin C. (RAND Corporation, 2023)
Cyberspace, where information--and hence serious value--is stored and manipulated, is a tempting target. An attacker could be a person, group, or state and may disrupt or corrupt the systems from which cyberspace is built. When states are involved, it is tempting to compare fights to warfare, but there are important differences. The author addresses these differences and ways the United States protect itself in the face of attack.